Contributory determinants influencing total assets of commercial banks in Malaysia (2008 - 2010) / Hasroleffendy Hassan, Maznah Wan Omar, Ahmad Yumni Abu Bakar - Hassan, Hasroleffendy; Wan Omar, Maznah; Abu Bakar, Ahmad Yumni (Institute of Research Management & Innovation (IRMI), 2012)
In tandem with the impending full liberalization of global economy and Basel III requirements in 2015, most commercial banks worldwide might encounter the risks of being taken over by larger bank given that the entry of larger foreign banks into local industries can no longer be restricted. Size of a bank is founded on the volume of its total assets. Therefore, it is imperative for commercial banks to be in the know about the macroeconomic factors that might affect their total assets. In this dissertation, macroeconomic determinants of total assets volume for commercial banks in Malaysia was scrutinized in 2008 - 2010 intervals (post 2008 financial turmoil) via quarterly data through multi-variate single-equation regression method and correlation. Regression results advocate that all the macroeconomic determinants in this thesis have statistically significant impact on total assets of the banks. The empirical findings demonstrate that Base Lending Rate (BLR) together with Foreign Exchange Rate (FER) are negatively interrelated to total assets of the banks. On the contrary, Foreign Direct Investment (FDI) has positive relationship with the same dependent variable (DV). The most influential factor against total assets of the banks is BLR. Albeit correlations techniques in this paper signify that BLR, FER as well as FDI have not significantly explained the variations in total assets of the Malaysian banking sector, it is noteworthy that the empirical findings produce similar results as regression methods whereby BLR and FER are negatively correlated to total assets whereas FDI has positive relationship with total assets.